2019
DOI: 10.3389/fonc.2019.00447
|View full text |Cite|
|
Sign up to set email alerts
|

The Prognostic and Therapeutic Potential of LRIG3 and Soluble LRIG3 in Glioblastoma

Abstract: Glioblastoma is a highly lethal type of primary brain tumor that exhibits unrestricted growth and aggressive invasion capabilities, leading to a dismal prognosis despite a multitude of therapies. Multiple alterations in the expression level of genes and/or proteins have been identified in glioblastomas, including the activation of oncogenes and/or silencing of tumor-suppressor genes. Nevertheless, there are still no effective targeted therapies associated with these changes. In this study, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…On the contrary, LRIG2 interacts with EGFR directly and promotes activation of the downstream signaling pathway (29). Besides, LRIG3 can inhibit activation of the Ras/ ERK and PI3K/AKT pathways in glioma, indicating that LRIG3, similar to LRIG1, may have an antagonistic effect against LRIG2 (13,14). Moreover, Zeng et al showed that LRIG3 is required for the interaction between Dual-specificity phosphatase 6 (DUSP6) and ERK in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, LRIG2 interacts with EGFR directly and promotes activation of the downstream signaling pathway (29). Besides, LRIG3 can inhibit activation of the Ras/ ERK and PI3K/AKT pathways in glioma, indicating that LRIG3, similar to LRIG1, may have an antagonistic effect against LRIG2 (13,14). Moreover, Zeng et al showed that LRIG3 is required for the interaction between Dual-specificity phosphatase 6 (DUSP6) and ERK in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical assays were performed on glioma and mouse xenograft tumor tissues as previously described ( 14 ). Expression levels of labeling were stratified and scored according to the following grading system: staining extensity was categorized as 1 (≤ 10% positive cells), 2 (< 10% and ≤ 30% positive cells), 3 (< 30 and ≤ 50% positive cells) or 4 (> 50% positive cells), whereas staining intensity was categorized as 0 (negative), 1 (weak), 2 (moderate) or 3 (strong).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hellström et al reported that LRIG3 was lowly expressed in adult mouse hearts and influenced heart function and plasma lipid levels . In cancer, LRIG3 was shown to be significantly decreased in cervical squamous cell carcinoma and glioblastoma . However, the expression level, biological function, and clinical implication of LRIG3 in CRC remain unknown.…”
Section: Introductionmentioning
confidence: 99%